GUIDANCE EVALUATION ANALYSIS STUDY PROGRAM FIELD WORK PRACTICES INFORMATION ENGINEERING DURING PANDEMIC - Sri Lestanti (JOSAR (Journal of Students Academic Research), 2021)
PKL or Field Work Practice is a final semester student activity carried out with the aim of channeling and improving skills and abilities in the field of study being taken. In carrying out PKL activities, students must have a supervisor during carrying out PKL activities. PKL guidance is an activity that is very much needed for a student to support the smooth running of street vendors and at the time of preparing street vendors reports. According to the results of Ethics research (2016), there are several things that make it difficult for students in conducting PKL guidance in compiling PKL reports including determining the title of the report, lack of references, lack of working time, feeling lazy to work and lack of motivation, lecturers who are difficult to find, difficult to divide time. , work fatigue, insufficient rest time. Therefore, there is a need for research using descriptive quantitative methods. Based on the research that has been done, it can be concluded that the process of mentoring street vendors during the pandemic is still running smoothly and does not really affect the decrease in satisfaction for students. From the results of the research, students gave a good response of 37%, very good 40%, quite 12%, less 7% and very less 4%. So that the overall aspects of PKL guidance given by lecturers to students can be concluded that students are satisfied with a very good level of 40%.